The Impact of COVID-19 on Higher Education : Challenges and Issues (Comparative & International Education Series, 2021)
This chapter gives an overview of the novel coronavirus (COVID-19) in higher education and how colleges and universities have changed and adjusted along with new technology and challenges. In this book, we have tried to respond to the growing need for new insights and perspectives to improve higher education policy and practice in the era of COVID-19. The need to understand the impact of COVID-19 on higher education is more urgent as institutions seek to innovate and adapt during times of uncertainty.How to cite this chapter:Ammigan, R., Chan, R. Y., & Bista, K. (2022). The impact of COVID-19 on higher education: Challenges and issues. In  R. Ammigan, R. Y. Chan, & K. Bista, (eds)., COVID-19 and higher education in the global context: Exploring contemporary issues and challenges (pp. 1-8). STAR Scholars. https://starscholars.org/product/covid-19-and-higed/